2013
DOI: 10.1007/s00467-013-2524-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel urinary biomarker profile to identify acute kidney injury (AKI) in critically ill neonates: a pilot study

Abstract: Background The goal of this study was to assess the value of a urinary biomarker profile comprised of Neutrophil Gelatinase-associated Lipocalin (NGAL), Fibroblast Growth Factor-2 (FGF-2), and Epidermal Growth Factor (EGF), to detect acute kidney injury (AKI) in critically ill neonates. Methods We conducted a prospective cohort pilot study of at-risk neonates treated in a level IIIC neonatal intensive care unit (NICU) with therapeutic hypothermia (HT) (n = 25) or extracorporeal membrane oxygenation (ECMO) (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
(54 reference statements)
1
27
1
Order By: Relevance
“…The trough levels of gentamicin were measured in samples drawn 30 min before the daily doses of gentamicin were given. In a separate prospective study involving a subset ( n = 25) of patients enrolled in the current study and 27 healthy controls, urinary biomarkers were assessed during the first week of life as described previously [26]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The trough levels of gentamicin were measured in samples drawn 30 min before the daily doses of gentamicin were given. In a separate prospective study involving a subset ( n = 25) of patients enrolled in the current study and 27 healthy controls, urinary biomarkers were assessed during the first week of life as described previously [26]. …”
Section: Methodsmentioning
confidence: 99%
“…The third group, named the delayed rise in eCrCl (DReCrCl) group, included the remaining newborns who failed to increase their eCrCl by >50 % from birth to the 7th day of life and/or showed elevated SCr values at this time point. This eCrCl cutoff point was associated with changes in urinary biomarkers of AKI in newborns with HIE [26] and may be analogous to the pRIFLE injury criteria, which require an eCrCl decrease of 50 %, and correlates with a worse clinical outcome of critically ill children [11]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior literature has shown that in premature infants without AKI, urine proteins will be highest among those with the lowest GA, probably because of the passive loss of proteins in the context of immature tubular function (6)(7)(8). Previously, we (7) and others (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have published data on the ability of urine biomarkers to predict AKI in neonates; however, these studies are limited by the size of the cohort or the use of nested case-control methods, with most of these studies evaluating only one biomarker. In addition, previous studies were subject to risk of misclassification bias, given that many infants had only a few SCr levels measured to determine AKI.…”
Section: Introductionmentioning
confidence: 99%